Single-step fabrication and work function engineering of Langmuir-Blodgett assembled few-layer graphene films with Li and Au salts - Ivana R. Milošević (Nature Portfolio, 2020)
Abstract To implement large-area solution-processed graphene films in low-cost transparent conductor applications, it is necessary to have the control over the work function (WF) of the film. In this study we demonstrate a straightforward single-step chemical approach for modulating the work function of graphene films. In our approach, chemical doping of the film is introduced at the moment of its formation. The films are self-assembled from liquid-phase exfoliated few-layer graphene sheet dispersions by Langmuir-Blodgett technique at the water-air interfaces. To achieve a single-step chemical doping, metal standard solutions are introduced instead of water. Li standard solutions (LiCl, LiNO3, Li2CO3) were used as n-dopant, and gold standard solution, H(AuCl4), as p-dopant. Li based salts decrease the work function, while Au based salts increase the work function of the entire film. The maximal doping in both directions yields a significant range of around 0.7 eV for the work function modulation. In all cases when Li-based salts are introduced, electrical properties of the film deteriorate. Further, lithium nitrate (LiNO3) was selected as the best choice for n-type doping since it provides the largest work function modulation (by 400 meV), and the least influence on the electrical properties of the film.